(untitled) (Web of Teachers: Inderscience Research, 2023)
The use of new pedagogical educational technologies to shape the professional activity of future chemistry teachers - interactive method, didactic games, cooperative teaching - content of test lessons is included. Information on the development of professional competence and adaptation to the world education structure, the use of new pedagogical technologies in the teaching of theoretical issues of chemistry, handouts for independent work are aimed at shaping the professional activity of future chemistry teachers.